Use of Liquid Organic Fertilizer from Kepok Banana Peel (Musa acuminata) on the Growth of Mustard Plants (Brassica juncea) - Ranti An Nisaa; Maryanti Setyaningsih; Dewi Anugrah; Tri Utami Dewi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Banana peel waste is one of the contributors to organic waste in Indonesia. By using banana peels as fertilizer, it is hoped that organic waste can be reduced. This research aims to determine the effect of Liquid Organic Fertilizer (LOF) from kepok banana peel (Musa acuminata) on the growth of mustard greens (Brassica juncea), using an experimental method with a Completely Randomized Design (CRD) consisting of 5 treatments with 4 replications, namely P0: control group (without banana peel waste LOF), P1 = 25 ml LOF, P2 = 50 ml LOF, P3 = 75 ml LOF, and P4 = 100 ml LOF. The parameters observed were plant height, number of leaves, and wet weight. The research data were analyzed using the ANOVA test with a significance level of 5% followed by the DMRT/Duncan test to determine the differences in effects between treatments. Giving 75 ml of banana peel LOF had the most effective effect with an average plant height of 16.75 cm, an average number of leaves of 7, and an average wet weight of 2.25 gr. From the results of the ANOVA test, the plant height was 7.95, the number of leaves was 1.17, and the wet weight was 16.00. From the three parameters, it was found that Fcount>Ftable (2.87) so it was concluded that giving 75 ml LOF of kepok banana peel had a significant effect on the vegetative growth of mustard plants compared to other treatments, especially on the parameters of plant height and fresh weight.